Distinct Proteomic Profiling of Plasma Extracellular Vesicles from Moderate-to-Severe Atopic Dermatitis Patients - Chang, Chih-Jung; Wang, Hai-Qing; Zhang, Jing; Zou, Ying; Zhang, Yi-Hua; Chen, Jia-Wen; Chen, Chun-Bing; Chung, Wen-Hung; Ji, Chao (Clinical, cosmetic and investigational dermatology, 2021)
Atopic dermatitis (AD) is a chronic, inflammatory cutaneous disorder characterized by a T helper 2 (Th2) immune response phenotype. Extracellular vesicles (EVs) are a heterogeneous family of cell-derived membranous structures, which transport cellular components such as DNA and proteins, and are involved in multiple physiological and pathological processes. Increasing evidence has shown that EVs secretion took part in the pathogenesis of AD. However, the proteomic studies of plasma-derived EVs in AD patients have not been reported. In this study, we investigated the diversity of plasma EVs collected from AD patients and healthy individuals and suggested that the candidates for uniquely or differentially expressed proteins in plasma EVs could be a diagnostic marker in AD. The plasma EVs were collected from 12 patients with moderate-to-severe AD and 13 healthy subjects. Proteomic analysis was performed by using a comprehensive nanoLC‑MS/MS method. Proteomic analysis revealed that a total of 1478 proteins in plasma EVs were found to be common proteins in AD, whereas a total of 1597 proteins in plasma EVs were found to be common proteins in HC. Eighty-six proteins in plasma EVs showed more than 2.5-fold up-regulation, while a total of 225 proteins in plasma EVs showed less than 1/2.5-fold down-regulation with a significant difference (p < 0.05) among AD compared with HC. The candidates for differentially expressed proteins in plasma EVs have been described as a connectivity PPI network related to several KEGG pathways, including pathways in platelet activation, complement, and so on. SLP-76 tyrosine phosphoprotein (SLP76) involved in platelet activation may significantly contribute to the pathogenesis of AD. We will further verify the role of SLP67 in AD via animal and cell experiments to provide a promising therapeutic or diagnostic target.